Softball Batting Exercise Model for Beginner Athletes - Muhammad Fahrezi Harahap; Iman Sulaiman; Yasep Setiakarnawijaya (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This research and development was conducted to produce exercise model of softball batting based on drill for beginner athletes by testing the effectiveness of softball batting training for beginner athletes. The development method used took the steps of Borg and Gall. To support data to be more valid, the process of analyzing data collection used observation, interviews, and tests. The batting exercise model was designed by combining drill-based training activities. After that the model item design was validated by 3 experts in their field, 1 softball lecturer, 1 softball coach, and 1 motor expert. The study involved 20 athletes consisting of 3 softball clubs in Medan. Increasing battingsoftball training during the pre-test showed t-count = -21,225, df = 19 and p-value = 0,00 <0,05, meaning that there were significant differences in softball batting training model before and after being given a training model. It could be concluded that the model of training developed effectively to enhance batting exercises developed was effective for enhancing batting exercises for beginner athletes.